The 'Antibiotic Apocalypse' – Scaremongering or Scientific Reporting?. Issue 3 (March 2017) - Cox, Jonathan A.G.; Worthington, Tony
Abstract : Antimicrobial resistance is dominating scientific media. We are warned of an impending 'antibiotic apocalypse', where mankind faces its biggest threat, untreatable microbes. However, the world is not ending. Scientists are responding to the threat; new knowledge and chemotherapeutics are being created to safeguard our future. The future is bright, not gloomy.